An Investigation on the Effect of the Difficulty of an Item in A Multiple Choice Examination When Item Choices are Rearrange - Pimentel, Jonald; Villaruz, Marah Luriely A. (Advances in Social Sciences Research Journal, 2021)
A study was conducted to know if rearranging item choices in an item of a multiple choice test affects the behavior of the examinees the way they look at the item difficulty of the given items. Two sets of test instruments (pretest and modified posttest) containing fifteen items were made with the same items but item choices for the modified posttest instrument were rearranged. Among the 205 examinees who took the test during a two-week time interval, their responses were modeled using the Rasch model. Results show that the estimates of the item difficulties for the majority of the fifteen items between the two tests were different. Majority of the items given in the exam showed an increase in the difficulty level as viewed by the examinees. The effect on the difficulty maybe due to the time interval the two sets of test were administered, that is first, students forget what they learned and see the items as difficult (time factor) and second, the rearrangement of the choices in each items in the post test affected the student’s way they see in dealing the items of the test which partly contributed to the increase of the level of difficulty of majority of the items in the test.